Large Fizeau’s light-dragging effect in a moving electromagnetically induced transparent medium - Pei-Chen Kuan (Nature Portfolio, 2016)
Phase velocity of light can be slowed down when passing through a moving medium. Here the authors demonstrate a light dragging effect enhanced by three orders of magnitude over previous reports by using electromagnetically induced transparency in cold Rubidium atoms and utilize this effect for motion sensors.